2012
DOI: 10.4161/auto.22145
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of TNFSF10/TRAIL-induced apoptosis by an autophagic survival pathway involving TRAF2- and RIPK1/RIP1-mediated MAPK8/JNK activation

Abstract: Although it is known that tumor necrosis factor-related apoptosis-inducing ligand (TNFSF10/TRAIL) induces autophagy, the mechanism by which autophagy is activated by TNFSF10 is still elusive. In this report, we show evidence that TRAF2- and RIPK1-mediated MAPK8/JNK activation is required for TNFSF10-induced cytoprotective autophagy. TNFSF10 activated autophagy rapidly in cancer cell lines derived from lung, bladder and prostate tumors. Blocking autophagy with either pharmacological inhibitors or siRNAs targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
120
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 39 publications
8
120
0
Order By: Relevance
“…Further, JNK inhibitor attenuated Bcl-2 reduction. While previous studies have shown that Bcl-2 phosphorylation can disrupt the Bcl-2/Beclin1 complex for autophagy activation [30] , we recently found that the JNKmediated degradation of Bcl-2 also leads to the induction of autophagy [31] . Thus, it is possible to conclude that JNKmediated Bcl-2 degradation results in Beclin1-mediated autophagy activation in ROS-treated MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, JNK inhibitor attenuated Bcl-2 reduction. While previous studies have shown that Bcl-2 phosphorylation can disrupt the Bcl-2/Beclin1 complex for autophagy activation [30] , we recently found that the JNKmediated degradation of Bcl-2 also leads to the induction of autophagy [31] . Thus, it is possible to conclude that JNKmediated Bcl-2 degradation results in Beclin1-mediated autophagy activation in ROS-treated MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we clearly demonstrate that H 2 O 2 induces autophagy in MSCs, including increased LC3-II expression, decreased p62 expression, and autophagic flux. Autophagy can mediate cell survival or death, depending on the cell type, environment and stimulation [31,38,39] . The role of ROS-induced autophagy in MSCs is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[65][66][67][68] The antiapoptotic BCL2 family proteins, such as BCL2, bind beclin-1 (BECN1) to inhibit autophagy, and the dissociation of BCL2 family proteins from BECN1 promotes autophagy. [69][70][71] Because MCF-7 human breast carcinoma cells do not express caspase-3, earlier studies have shown that TNFSF10 induces autophagy in MCF-7 cells, and autophagy is protective against the cytotoxicity of TNFSF10 in these cells, 72 the prominent augmentation of TNFSF10 gene expression is accompanied by a severe inhibition of BCL2 (11-fold downregulation vs. metformin-naïve MCF-7 cells), which strongly suggests that the activation of protective autophagy plays a causative role in the acquisition of resistance to metformin. The metformin-refractory MCF-7/MET-R cells also activated (14-fold vs. metformin-naïve MCF-7 cells) the expression of TNFAIP2, which encodes tumor necrosis factor Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…TNFSF10 can trigger cell survival and proliferation through NFKB/nuclear factor kappa B and/or MAPK8 (mitogen-activated protein kinase 8)-mediated cytoprotective autophagy. 52 Further investigation of the TNFSF10/TRAIL-MAPK8-autophagy axis in alveolar ridge tumors may reveal a cell-type dependent role for autophagy in the pathogenesis of these rare but aggressive tumors.…”
mentioning
confidence: 99%